2016
DOI: 10.1155/2016/1492743
|View full text |Cite
|
Sign up to set email alerts
|

Podocyturia: A Clue for the Rational Use of Amiloride in Alport Renal Disease

Abstract: No specific or efficient treatment exists for Alport syndrome, an X-linked hereditary disease caused by mutations in collagen type IV, a crucial component of the glomerular basement membrane. Kidney failure is usually a major complication of the disease, and patients require renal replacement therapy early in life. Microhematuria and subsequently proteinuria are hallmarks of kidney involvement, which are due to primary basement membrane alterations that mainly cause endothelial thrombosis and podocyte contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…The same applies for proteinuria, nil or low at initial stages, and comparatively higher at later stages[ 26 ]. Podocyturia has been assessed in a wide variety of glomerulopathies, as well as in transplantation and in entities where the glomerulus is not primarily affected, as in polycystic kidney disease[ 26 , 27 , 29 , 30 , 37 , 38 ].…”
Section: Search For Podocyturia: Potentialitymentioning
confidence: 99%
“…The same applies for proteinuria, nil or low at initial stages, and comparatively higher at later stages[ 26 ]. Podocyturia has been assessed in a wide variety of glomerulopathies, as well as in transplantation and in entities where the glomerulus is not primarily affected, as in polycystic kidney disease[ 26 , 27 , 29 , 30 , 37 , 38 ].…”
Section: Search For Podocyturia: Potentialitymentioning
confidence: 99%
“…In patients with cancer, CD39-expressing Th17 cells predict poor clinical outcome. 81 Th17 cells generated in the absence of TGF-β that lack CD39 and CD73 fail to promote tumor growth and are endowed with antitumor functions. 82 Several studies suggest that Th17 and IL-17A promote antitumor immune responses.…”
Section: Cd39 and Th17 Responsesmentioning
confidence: 99%
“…In our cell lines, the co‐expression of a marker of immature podocytes such as PAX2 along with COL4 α3, α4, and α5 collagen chains could suggest a progenitor stage; however, as proven for other ATS‐related disorders such as focal glomerular sclerosis (Bariety et al., ; Barisoni et al., ), it is likely that the impaired podocytes encounter a process of dysregulation and dedifferentiated and then re‐express markers of immature cells such as PAX2 as in fetal glomeruli. Podocyturia has been previously reported to be an indicator of early glomerular damage (Trimarchi et al., ; Vogelmann et al., ). In line with this hypothesis, we were not able to isolate urine‐derived cell lines from healthy individuals (Table ) confirming that a GBM damage is necessary for podocytes‐lineage cells to be filtered through the glomerulus and thus that podocyturia can be used as biomarker of disease progression and response to treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Commonly drug‐based approaches in ATS include angiotensin‐converting enzyme inhibitor (ACE‐I) and angiotensin receptor blockers, which are employed to reduce proteinuria and thus retard kidney disease progression and cardiovascular morbidity and mortality. Conventional treatment is commonly started for urinary proteins/urinary creatinine levels above 0.2 mg. A recent case report indicated that low‐dosage Amiloride treatment, acting in the very early stage of disease, is able to decrease podocyturia in an ATS patient (Trimarchi et al., ), Therefore, our cell line provides a clean system to test for the effect of repurposing of Amiloride or other drugs on disease‐relevant cell lines and to evaluate the possibility of a patophysiologically based therapeutic approach. The possibility of directly reverting collagen IV causative mutations in ATS injured podocytes has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation